Peningkatan Daya Tarik Produk UMKM Teh Sereh Seungit dengan Kemasan Kekinian - Nicole Sadjoli; Retno Yuliati; William Reynaldi; Stefany Dewi Anggraini; Rinaldy Debian; Stefanus Yedidya; Henrikus Kenneth (Journal of Dedicators Community, 2019)
Expanding the distribution of product sales to souvenir outlets around Cianjur Regency is a challenge for business partners. Especially if the partner's products do not have selling value because they do not have a brand name, uninteresting packaging, and have no PIRT permit. Moreover, the limitation of the partner is in utilizing technology to support operations and marketing. In community development activity, we have the opportunity to assist partners to increase the attractiveness and selling value of products so that their products can be accepted at souvenir outlets around Ciputri and Cianjur Villages. In addition, we help partners to enhance thier capabilities in technical knowledge and use of technology for operational and promotion. The results of this activity are the product has a brand name and product labels, the creation of innovative, attractive, and nowadays packaging, obtaining PIRT certificates, and finally can sell and diplay the product in the famous souvenir outlets  in Cianjur. Besides, increasing partner skills in the use of technology for purchasing production materials and marketing. After the community development activities and mentoring period are over, it is expected to provide benefits for partners to independently expand product distribution to souvenir shops around Cianjur so that they can increase sales and the economy of partner families. Besides, partners can independently use e-commerce and social media as a means of promotion and sales.